Detection of dicistroviruses RNA in blood of febrile Tanzanian children. Issue 1 (1st January 2019) - Cordey, Samuel; Laubscher, Florian; Hartley, Mary-Anne; Junier, Thomas; Pérez-Rodriguez, Francisco J.; Keitel, Kristina; Vieille, Gael; Samaka, Josephine; Mlaganile, Tarsis; Kagoro, Frank; Boillat-Blanco, Noémie; Mbarack, Zainab; et al.
ABSTRACT: Fever is the leading cause of paediatric outpatient consultations in Sub-Saharan Africa. Although most are suspected to be of viral origin, a putative causative pathogen is not identified in over a quarter of these febrile episodes. Using a de novo assembly sequencing approach, we report the detection (15.4%) of dicistroviruses (DicV) RNA in sera collected from 692 febrile Tanzanian children. In contrast, DicV RNA was only detected in 1/77 (1.3%) plasma samples from febrile Tanzanian adults, suggesting that children could represent the primary susceptible population. Estimated viral load by specific quantitative real-time RT–PCR assay ranged from < 1.32E3 to 1.44E7 viral RNA copies/mL serum. Three DicV full-length genomes were obtained, and a phylogenetic analyse on the capsid region showed the presence of two clusters representing tentative novel genus. Although DicV-positive cases were detected throughout the year, a significantly higher positivity rate was observed during the rainy season. This study reveals that novel DicV RNA is frequently detected in the blood of Tanzanian children, paving the way for further investigations to determine if DicV possibly represent a new agent in humans.